Assessing the determinants of oral health-related quality of life among male costa rican students : findings from a cross-sectional study = Evaluación de los determinantes de la calidad de vida relacionada con la salud bucal entre estudiantes varones costarricenses : hallazgos de un estudio transversal - Reyes Umaña, Yuliana 1996-
To evaluate the association between socioeconomic, psychosocial, and lifestyle factors with Oral Health-Related Quality of Life (OHRQoL) in a sample of adolescent males from Colegio Técnico San Agustín de Cartago - Ciudad de los Niños (St. Augustine's Technical High School), located in the Cartago Province of Costa Rica. Data for this study were obtained from a descriptive, cross-sectional study conducted in 2019. The sample consisted of 394 adolescent males aged between 12 and 22 years. OHRQoL was assessed using the validated Spanish version of the Oral Health Impact Profile (OHIP-49). The following variables were considered: age, parental education, having a remunerated job, Health-Related Quality of Life (measured via the SF-36 questionnaire), self-esteem (Rosenberg scale), perceived stress (PSS-14), depression (CES-D), physical activity, history of dropping out of school, flossing and tooth-brushing habits, eating snacks between meals, medication intake for illness, having received oral health care instructions, history of dental visits due to pain, frequency of dental visits, history of childhood tooth decay, and access to dental health care during childhood. Qualitative variables were analyzed using the Student's t-test, while Pearson correlation was used for quantitative variables. Multivariable analysis was performed using linear regression. Statistical significance was set at p<0.05 using STATA 14®. Enhanced general health-related quality of life (p<0.01) and early childhood dental attendance (p<0.01) were identified as factors associated with improved OHRQoL. Conversely, having had dental visits for pain (p<0.01), elevated depression symptomatology (p<0.01), and a history of childhood dental cavities (p<0.01) were all associated with worse OHRQoL. This study suggests a link between general and oral health. Experiences during childhood appear to set a standard for adolescence. Lastly, it is crucial to note the significant impact of mental...